Mortality in Patients Admitted for Concurrent COPD Exacerbation and Pneumonia. (2nd January 2017) - Sharafkhaneh, Amir; Spiegelman, Andrew M.; Main, Kevin; Tavakoli-Tabasi, Shahriar; Lan, Charlie; Musher, Daniel
ABSTRACT: It is unclear whether concurrent pneumonia and chronic obstructive pulmonary disease (COPD) have a higher mortality than either condition alone. Further, it is unknown how this interaction changes over time. We explored the effect of pneumonia and COPD on inpatient, 30-day and overall mortality. We used a Veterans Health Affairs database to compare patients who were hospitalized for a COPD exacerbation without pneumonia (AECOPD), patients hospitalized for pneumonia without COPD (PNA) and patients hospitalized for pneumonia who had a concurrent diagnosis of COPD (PCOPD). We studied records of 15, 065 patients with the following primary discharge diagnoses: (a) AECOPD cohort (7, 154 individuals); (b) PNA cohort (4, 433 individuals); and (c) PCOPD (3, 478 individuals), comparing inpatient, 30-day and overall mortality in the three study cohorts. We observed a stepwise increase in inpatient mortality for AECOPD, PNA and PCOPD (4.8%, 9.5% and 13.2%, respectively). These differences persisted at 30 days post-discharge (AECOPD = 6.7%, PNA = 12.4% and PCOPD = 14.6%; p < 0.0001), but not throughout the study period (median follow-up: 37 months). With time, the death rate rose disproportionally in patients who had been admitted for AECOPD (AECOPD = 64.5%; PNA = 57.4% and PCOPD 66.2%; p < 0.001). In multivariate analysis, PCOPD predicted the greatest inpatient mortality ( p < 0.001). The data showed a progression in inpatient and 30-day mortality from AECOPD to PNA to PCOPD. Pneumonia and COPD differentially affected inpatient, 30-day and overall mortality with pneumonia affecting predominantly inpatient and 30-day mortality while COPD affecting the overall mortality.